Relationship between Organizational Culture and Employee Performance at the Inpatient Installation of Muhammadiyah Kediri Hospital - Ansarul Fahrudda; Mirrah Samiyah; Linda Hapsari (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2024)
Public demand for the quality of hospital services causes the need to improve service performance at Muhammadiyah Kediri Hospital. The Inpatient Installation as the unit that interacts the most with customers is very prone to complaints which must be a priority in improving service performance by implementing organizational culture innovation. The purpose of this study is to determine the relationship between organizational culture and employee performance at the Inpatient Installation of Muhammadiyah Kediri Hospital. This study used an observational quantitative design with a cross-sectional study approach with univariate data frequency distribution analysis and bivariate data analysis using the Spearman Rho Test. The population in this study were all employees of the Inpatient Installation of Muhammadiyah Kediri Hospital with a sample of 70 respondents taken using purposive sampling method with the Slovin formula. The instrument used in this study was a questionnaire. The results of univariate analysis obtained good and very good organizational culture by 61.4%, good and very good employee performance by 61.4%. The results of the Spearman Rho bivariate analysis obtained the coefficient value is 0.889, so it is concluded that there is a significant relationship between organizational culture and employee performance in the Inpatient Installation and is in the strong category.